A method for producing stone-like concrete pavement bricks and panels from chromium slag

CN122977783APending Publication Date: 2026-10-27ZHEJIANG XINGCHUANG ENVIRONMENTAL PROTECTION GROUP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611101048.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该方法稳定性好,但能耗极高、设备投资大,经济性较差,难以大规模推广

Benefits of technology

(1)本发明采用生物质还原剂异山梨醇替代传统亚硫酸钠、硫酸亚铁等无机还原剂。异山梨醇具有独特的双环醚二醇刚性结构,在pH2.0-2.5酸性条件下,其仲羟基被重铬酸根氧化为内酯/羰基,六价铬不可逆还原为三价铬,反应彻底且产物为水溶性小分子内酯,不含铁、硫、锡等金属离子,避免了传统还原剂带来的二次沉淀、硫化氢异味及大量含铬污泥问题。还原后铬渣滤液六价铬浓度≤0.1mg/L,去除率≥99.5%;模拟酸雨环境浸泡72小时后三价铬浸出量≤0.05mg/L,长期环境稳定性显著优于传统工艺,从根本上消除了六价铬返黄与浸出超标风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977783A_ABST
    Figure CN122977783A_ABST
Patent Text Reader

Abstract

The application discloses a method for producing stone-like concrete pavement bricks and panels from chromium slag. The method first grinds and calcines the chromium slag to activate it, and then deeply reduces hexavalent chromium under acidic conditions by using high-purity isosorbide as a reducing agent, with a removal rate of greater than or equal to 99.5%. Then, fly ash and a composite alkali activator are added to the reduced slurry, and the slurry is solidified by pressure filtration to obtain high-strength low-toxicity solidified blocks. Finally, the solidified blocks are crushed into aggregates, mixed with muddy fine aggregates, cement, slag powder and the like, and formed into finished products by vacuum pressure filtration and curing. The obtained products have a 28d compressive strength of greater than or equal to 40 MPa, a flexural strength of greater than or equal to 4.0 MPa, and a hexavalent chromium leaching concentration of less than or equal to 0.05 mg / l, and have excellent mechanical properties and environmental safety. The application realizes the harmless and high-value resource treatment of chromium slag, and the process is stable and controllable, and is suitable for municipal road paving and landscape decoration fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hazardous waste resource utilization technology, specifically relating to a method for producing stone-like concrete paving bricks and panels by reducing chromium slag. More specifically, isosorbide is used to reduce harmful chromium slag, followed by the treatment of harmless chromium slag through an alkali activation-pressure filtration coupling process, and the treated product is then prepared into stone-like concrete. Background Technology

[0002] Chromium slag is a typical hazardous waste generated during the smelting of metallic chromium and the production of chromium salts. my country produces approximately 1 million tons annually, with historical stockpiles exceeding 6 million tons. Chromium slag contains hexavalent chromium compounds in various forms, including water-soluble and acid-soluble forms. Hexavalent chromium is highly toxic, carcinogenic, and mutagenic, and easily migrates and pollutes soil and groundwater under rainwater leaching. The wet detoxification method uses traditional reducing agents such as sodium sulfite, ferrous sulfate, and sodium sulfide to reduce hexavalent chromium to trivalent chromium, but it suffers from problems such as high water consumption, generation of chromium-containing secondary wastewater, and poor stability of reduction products. Trivalent chromium is easily re-oxidized back to hexavalent chromium in long-term open-air environments, leading to excessive leaching toxicity. Existing resource utilization technologies mostly use chromium slag in low-end applications such as roadbed backfilling and foundation blocks, with imperfect detoxification processes, high long-term environmental risks, and product mechanical properties and durability failing to meet building material standards.

[0003] Stone-like concrete is a decorative building material made by replacing natural stone with artificial aggregates. It combines the texture of natural stone with the mechanical properties of concrete and is widely used in road paving, landscaping, and building exteriors. Its production consumes a large amount of mineral aggregates and admixtures. If stone-like concrete could be prepared using harmless chromium slag as a raw material, it would reduce the consumption of natural resources and achieve high-value utilization of chromium slag. However, existing technologies are limited by problems such as incomplete chromium slag detoxification, high risk of hexavalent chromium leaching during long-term use, and low-end product positioning, preventing large-scale application. While patents CN11062.7448B, CN114804814A, CN108439836B, and CN119080452A disclose chromium slag-based concrete preparation technologies, they all use traditional inorganic reducing agents, resulting in common defects such as low reduction efficiency, heavy secondary pollution, large sludge production, and a narrow applicable pH range (only highly efficient at pH < 3). These technologies cannot simultaneously meet the requirements of deep detoxification, long-term stability, and the preparation of high-value stone-like products.

[0004] Currently, the mainstream methods for disposing of chromium slag include three categories: wet detoxification, solidification and stabilization, and high-temperature melting.

[0005] Wet detoxification method: This method uses chemical reducing agents such as ferrous sulfate and sodium sulfite in acidic or neutral aqueous solutions to reduce hexavalent chromium to trivalent chromium, thus achieving detoxification. This method has high detoxification efficiency, but it suffers from drawbacks such as large amounts of reducing agents required, the generation of large amounts of chromium-containing wastewater requiring secondary treatment, the chromium slag remaining in loose powder form after treatment, poor long-term stability, and high treatment costs.

[0006] Solidification and stabilization method: Chromium slag is mixed with cement, lime, and other cementing materials, and chromium is fixed in the solidified body through physical encapsulation and chemical bonding. This method is simple to operate, but the solidified body expands significantly in volume. During long-term service, hexavalent chromium is at risk of re-dissolving under the effects of carbonization, freeze-thaw cycles, and acid rain erosion. In addition, the solidified body has low added value and is difficult to utilize as a resource.

[0007] High-temperature melting method: Chromium slag is melted and vitrified at temperatures above 1200℃, reducing hexavalent chromium and fixing it in the glass network. This method has good stability, but it consumes a lot of energy, requires large equipment investment, and has poor economic efficiency, making it difficult to promote on a large scale.

[0008] The above methods all have limitations to varying degrees: the wet detoxification method failed to solve the problem of resource utilization of chromium slag; the solidification and stabilization method has insufficient long-term stability and low product added value; and the high-temperature melting method has poor economic efficiency.

[0009] Therefore, there is an urgent need to develop a chromium slag resource utilization technology that integrates deep reduction of hexavalent chromium, long-term stable solidification, and high-performance stone-like concrete preparation. This technology can completely detoxify chromium slag and transform it into high-value-added building materials, fundamentally solving the environmental risks and resource waste problems associated with chromium slag. Summary of the Invention

[0010] To address the aforementioned problems, this invention provides a method for producing stone-like concrete paving bricks and panels using reduced chromium slag.

[0011] Specifically, it includes the following steps: S1 Chromium Slag Deep Reduction and Detoxification: The original chromium slag is crushed and ground to a particle size ≤0.075mm, and then calcined and activated at 400-450℃ for 1-2 hours to obtain activated chromium slag powder. The activated chromium slag powder is mixed with water to make a slurry, the pH of the slurry is adjusted to 2.0-2.5, isosorbide is added as a reducing agent, and the mixture is stirred and reacted at 80-90℃ for 2-4 hours. During the reaction, samples are taken every 30-40 minutes to detect the hexavalent chromium content until the hexavalent chromium concentration in the filtrate is ≤0.1mg / L, thus reducing hexavalent chromium to trivalent chromium, to obtain reduced chromium slag slurry. The removal rate of hexavalent chromium in the filtrate of the reduced chromium slag slurry is ≥99.5%. The mass ratio of isosorbide to hexavalent chromium in the original chromium slag is (3-5):1.

[0012] S2 Alkali Activation-Filtration Coupled Curing: Fly ash and a composite alkali activator are added to the reduced chromium slag slurry obtained in step S1, and the mixture is stirred evenly to obtain an alkali-activated slurry. The alkali-activated slurry is injected into a diaphragm filter press and cured under a pressure of 1.5-2.5 MPa for 20-40 minutes. After demolding, the resulting cured block is cured for 28 days at a temperature of 20±2℃ and a relative humidity of ≥95% to obtain a cured block with a moisture content of ≤15%. The composite alkali activator is composed of sodium hydroxide, water glass, and calcium hydroxide.

[0013] Preparation of S3 Imitation Stone Concrete: The solidified blocks obtained in step S2 are crushed and sieved to obtain coarse aggregate and fine aggregate of the solidified blocks. By weight, take 30-40 parts of coarse aggregate, 20-30 parts of fine aggregate, 10-20 parts of mud-containing fine aggregate, 15-25 parts of cement, 5-10 parts of slag powder, and 8-12 parts of water, mix them evenly, pour them into a mold, and then vacuum press-filter and cure to obtain imitation stone concrete paving bricks or panels. The mud-containing fine aggregate contains 25%-35% silt by weight.

[0014] Specifically, the original chromium slag mentioned in step S1 is wet or dry chromium slag that has not undergone high-temperature melting treatment, and its hexavalent chromium content is 500-3000 mg / kg.

[0015] Specifically, the isosorbide mentioned in step S1 is self-made high-purity isosorbide with a purity ≥99%.

[0016] Specifically, the preparation method of isosorbide is as follows: using glucose as raw material, catalytic hydrogenation is carried out in the presence of Raney nickel catalyst at 3.0-3.2 MPa and 110-120℃. The reaction product is decolorized by activated carbon, concentrated under reduced pressure to a solid content of 70%, and then crystallized and dried.

[0017] Specifically, the Raney nickel catalyst is added at 5% of the glucose mass.

[0018] Specifically, the fly ash mentioned in step S2 is grade II or higher fly ash, and the amount added is 20%-40% of the dry basis mass of the reduced chromium slag.

[0019] Specifically, the mass ratio of sodium hydroxide, water glass, and calcium hydroxide in the composite alkali activator is (3-5):(4-6):(1-2), wherein the modulus of the water glass is 2.0-2.5.

[0020] Specifically, the total dosage of the composite alkali activator is 8%-15% of the dry weight of the reduced chromium slag.

[0021] Specifically, the 28-day compressive strength of the cured block obtained in step S2 is ≥30MPa, and the leaching toxicity of heavy metals meets the limit requirements of GB5085.3-2007 "Identification Standard for Hazardous Waste - Leaching Toxicity Identification".

[0022] Specifically, the fine aggregate containing mud mentioned in step S3 is obtained by naturally drying, crushing and sieving river dredging silt or engineering waste soil, with a particle size ≤4.75mm, and the SiO2 content in the silt ≤50% and the moisture content ≤60%.

[0023] Specifically, the cement is P·O42.5 ordinary Portland cement. The mixed raw materials also contain a polycarboxylate superplasticizer, the water reduction rate of which is ≥25%, and the dosage is 0.5%-1.0% of the cement mass.

[0024] Specifically, the process parameters for vacuum pressure filtration molding in step S3 are: vacuum degree -0.06-0.09MPa, pressure 1.0-2.0MPa, and pressure holding time 10-20min.

[0025] Specifically, the maintenance described in step S3 shall be carried out in any of the following ways: Standard maintenance: temperature 20±2℃, relative humidity ≥95%, maintenance period 7-28 days.

[0026] Steam curing: Temperature 60-80℃, curing for 6-12 hours, then switch to standard curing until 28 days old.

[0027] Specifically, the 28-day compressive strength of the imitation stone concrete paving bricks or panels obtained in step S3 is ≥40MPa, the flexural strength is ≥4.0MPa, and the hexavalent chromium leaching concentration is ≤0.05mg / L.

[0028] Specifically, the test method for the hexavalent chromium leaching concentration is performed in accordance with HJ / T299, "Identification of Leaching Toxicity of Solid Waste by Sulfuric Acid and Nitric Acid Method".

[0029] A method for producing stone-like concrete paving bricks and panels by reducing chromium slag.

[0030] It has the following beneficial effects: (1) This invention uses isosorbide, a biomass reducing agent, to replace traditional inorganic reducing agents such as sodium sulfite and ferrous sulfate. Isosorbide has a unique bicyclic ether diol rigid structure. Under acidic conditions of pH 2.0-2.5, its secondary hydroxyl group is oxidized by dichromate to lactone / carbonyl, and hexavalent chromium is irreversibly reduced to trivalent chromium. The reaction is thorough and the product is a water-soluble small molecule lactone, which does not contain metal ions such as iron, sulfur, and tin. This avoids the problems of secondary precipitation, hydrogen sulfide odor, and large amounts of chromium-containing sludge caused by traditional reducing agents. The concentration of hexavalent chromium in the chromium slag filtrate after reduction is ≤0.1mg / L, and the removal rate is ≥99.5%. After soaking in a simulated acid rain environment for 72 hours, the amount of trivalent chromium leached is ≤0.05mg / L. The long-term environmental stability is significantly better than that of traditional processes, fundamentally eliminating the risk of yellowing of hexavalent chromium and excessive leaching.

[0031] (2) This invention couples alkali-activated gelation with high-pressure membrane filtration. A composite alkali activator (sodium hydroxide, water glass, calcium hydroxide) synergistically activates the aluminosilicate components in chromium slag and fly ash, forming a dense solidified block in 20-40 minutes under a pressure of 1.5-2.5 MPa. The block has a moisture content of ≤15% and a 28-day compressive strength of ≥30 MPa. Compared with traditional natural curing or steam curing processes, the curing time is shortened by more than 90%, significantly improving production efficiency. At the same time, high-pressure filtration densifies the pore structure, further locking in heavy metal ions and enhancing the long-term stability of the solidified body.

[0032] (3) This invention uses 100% crushed and graded harmless solidified blocks as coarse and fine aggregates for the preparation of stone-like concrete. Chromium slag accounts for 60%-75% of the mass of the solidified blocks, completely replacing natural sand and gravel aggregates. At the same time, it introduces fine aggregate containing mud (silt content 25%-35%), breaking through the traditional restriction of prohibiting clay in concrete and further reducing raw material costs. The resulting stone-like concrete pavement bricks / panels have a 28-day compressive strength ≥40MPa, flexural strength ≥4.0MPa, frost resistance grade F200 or above, and impermeability grade P8 or above. The hexavalent chromium leaching concentration is ≤0.05mg / L. All properties meet the standards of municipal roads and landscape decoration projects, realizing the leap from landfill to stone-like building materials using chromium slag.

[0033] (4) The isosorbide of this invention is a biodegradable material that is non-toxic and non-corrosive. The solid powder does not oxidize or deliquesce at room temperature, and does not require antioxidant coating for long-term storage. This solves the industry pain points of easy oxidation and failure of ferrous sulfate and easy decomposition of sulfites. Its effective reducing pH range is 2-6, which is wider than the pH <3 limitation of traditional reducing agents. It can be adapted to chromium slag systems with different acidity and alkalinity, saving the cost of strong acid acidification. At the same time, it is applicable to multiple scenarios such as in-situ soil remediation and chromium reduction of cement powder, and has strong versatility.

[0034] (5) This invention uses conventional equipment such as reactors, diaphragm filter presses, and vacuum forming machines throughout the process, eliminating the need for additional dedicated environmental protection facilities; the filtrate is neutralized and recycled during the reduction stage, achieving zero wastewater discharge; the solidified blocks are used directly as aggregates, eliminating the high-energy-consuming steps of separate drying and grinding of chromium slag in traditional processes. Comprehensive calculations show that the cost per ton of chromium slag treated is reduced by more than 30% compared to the traditional wet detoxification-solidification process, achieving environmental, social, and economic benefits, and possessing feasibility for industrial-scale promotion. Attached Figure Description

[0035] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0036] Figure 1 This is a flowchart illustrating the steps of a method for producing imitation stone concrete paving bricks and panels using reduced chromium slag, as described in this invention. Detailed Implementation

[0037] It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of the invention.

[0038] The following detailed description of the implementation method of the present invention is in conjunction with the accompanying drawings. The description is only a partial embodiment and not all embodiments. For clarity, representations and descriptions unrelated to the present invention are omitted in the drawings and description.

[0039] To provide a clearer understanding of the technical features, objectives, and beneficial effects of this invention, the following detailed description of the technical solution is provided. Obviously, the described embodiments are only a portion of the embodiments of this invention, not all of them, and should not be construed as limiting the scope of implementation of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention.

[0040] Example 1 This embodiment provides a method for preparing stone-like concrete paving bricks and panels using isosorbide-reduced chromium slag. The specific steps are as follows: S1 Chromium Slag Pretreatment and Deep Reduction Detoxification Raw chromium slag (hexavalent chromium content 500-3000 mg / kg) is crushed and ground to a particle size ≤0.075 mm, then calcined and activated at 400-450℃ for 1-2 hours to obtain activated chromium slag powder. The activated chromium slag powder is mixed with water to form a slurry, and the pH of the slurry is adjusted to 2.0-2.5. Self-made isosorbide (≥99% purity) is added as a reducing agent, with a mass ratio of isosorbide to hexavalent chromium in the raw chromium slag of (3-5):1. The mixture is stirred and reacted at 80-90℃ for 2-4 hours. During the reaction, samples are taken every 30-40 minutes to detect the hexavalent chromium content until the concentration of hexavalent chromium in the filtrate is ≤0.1 mg / L, indicating that the hexavalent chromium has been reduced to trivalent chromium, resulting in a reduced chromium slag slurry with a hexavalent chromium removal rate ≥99.5%.

[0041] The method for preparing isosorbide is as follows: using glucose as raw material, adding 5% Raney nickel catalyst by weight of glucose, catalytic hydrogenation is carried out under the conditions of 3.0-3.2 MPa and 110-120℃. The reaction product is decolorized by activated carbon, concentrated under reduced pressure to a solid content of 70%, and then crystallized and dried to obtain isosorbide with a purity of ≥99%.

[0042] S2 Alkali Activation-Pressure Filtration Coupled Curing Add Grade II or higher fly ash (20%-40% of the dry weight of the reduced chromium slag) and a composite alkali activator (8%-15% of the dry weight of the reduced chromium slag) to the reduced chromium slag slurry obtained in step S1, and stir evenly to obtain an alkali-activated slurry. The composite alkali activator consists of sodium hydroxide, water glass (modulus 2.0-2.5), and calcium hydroxide, with a mass ratio of (3-5):(4-6):(1-2). Inject the alkali-activated slurry into a diaphragm filter press and filter-solidify under a pressure of 1.5-2.5 MPa for 20-40 minutes to obtain a solidified block with a moisture content ≤15%. The solidified block has a 28-day compressive strength ≥30 MPa, and the heavy metal leaching toxicity meets the limit requirements of GB5085.3 "Identification Standard for Hazardous Waste - Leaching Toxicity Identification".

[0043] S3 Stone-like Concrete Preparation The solidified blocks obtained in step S2 are crushed and sieved to obtain coarse aggregate and fine aggregate. By weight, take 30-40 parts of coarse aggregate, 20-30 parts of fine aggregate, 10-20 parts of silt-containing fine aggregate, 15-25 parts of P·O42.5 ordinary Portland cement, 5-10 parts of slag powder, and 8-12 parts of water. Simultaneously add 0.5%-1.0% of a polycarboxylate superplasticizer (water reduction rate ≥25%) by weight of the cement, mix thoroughly, and then pour into a mold. The silt-containing fine aggregate is obtained by naturally drying, crushing, and sieving river dredging silt or engineering waste soil, with a particle size ≤4.75mm, a silt content of 25%-35% by weight, a SiO2 content ≤50%, and a moisture content ≤60%.

[0044] The molding process employs vacuum pressure filtration, with a vacuum degree of -0.06 to -0.09 MPa, a pressure of 1.0 to 2.0 MPa, and a holding time of 10 to 20 minutes. After demolding, curing is performed using either of the following methods: standard curing (temperature 20±2℃, relative humidity ≥95%, curing age 7-28 days); or steam curing (temperature 60-80℃, curing for 6-12 hours, followed by standard curing up to 28 days). Upon completion of curing, the resulting stone-like concrete paving bricks or panels are obtained.

[0045] In this embodiment, the performance of the prepared stone-like concrete paving bricks or panels was tested, and the results are as follows: 28-day compressive strength: ≥40MPa; 28-day flexural strength: ≥4.0 MPa; Hexavalent chromium leaching concentration: ≤0.05mg / L (tested according to HJ / T299 "Identification of Toxicity of Leaching from Solid Waste by Sulfuric Acid and Nitric Acid Method").

[0046] All performance indicators meet the requirements of JC / T446-2000 "Concrete Pavement Bricks" and GB5085.3, and can be used as municipal road paving and landscape decorative panels.

[0047] Example 2 This embodiment is a specific implementation of Embodiment 1.

[0048] In this embodiment, the specific steps of the method for producing imitation stone concrete paving bricks and panels are as follows: S1 Chromium Slag Pretreatment and Deep Reduction Detoxification 500 kg of dry chromium slag (hexavalent chromium content 1800 mg / kg) stored in a chemical plant was taken, coarsely crushed by a jaw crusher, and then ground in a ball mill. After passing through a 200-mesh sieve, fine chromium slag powder with a particle size ≤0.075 mm was obtained, with a fineness compliance rate of 92%. The fine chromium slag powder was placed in a muffle furnace and calcined and activated at 420℃ for 1.5 h. After being removed and cooled to room temperature, activated chromium slag powder was obtained.

[0049] 400 kg of the above-mentioned active chromium slag powder was weighed and added to 800 L of deionized water for stirring and slurry preparation. The pH of the slurry was adjusted to 2.3 with 20% (w / w) dilute sulfuric acid. 2.7 kg of self-made high-purity isosorbide (purity ≥99%) was added to the slurry (the mass ratio of isosorbide to hexavalent chromium in the original chromium slag was 3.75:1). The temperature was raised to 85℃, and the mixture was stirred at 200 r / min for 3 h. Samples were taken every 35 min during the reaction, and the concentration of hexavalent chromium in the filtrate was detected using the diphenylcarbazide spectrophotometric method. After 2 h and 45 min of reaction, the concentration of hexavalent chromium in the filtrate dropped to 0.08 mg / L, which is lower than the limit of 0.1 mg / L specified in GB30760-2014. The reaction was then stopped, yielding reduced chromium slag slurry. The calculated hexavalent chromium removal rate was 99.6%.

[0050] The method for preparing high-purity isosorbide is as follows: 100 kg of glucose and 5 kg of Raney nickel catalyst (accounting for 5% of the glucose mass) are added to a high-pressure reactor. After replacing the air with hydrogen, the reactor is subjected to catalytic hydrogenation reaction at 3.1 MPa and 115 °C for 4 hours. The reaction solution is filtered to remove the catalyst, and 3 kg of activated carbon is added for decolorization for 1 hour. The solution is then concentrated under reduced pressure to a solid content of 70%. After cooling and crystallization, the solution is separated by centrifugation and dried under vacuum at 60 °C to obtain white needle-like crystals of isosorbide with a purity of 99.2%.

[0051] S2 Alkali Activation-Pressure Filtration Coupled Curing 120 kg of Grade II fly ash (30% of the dry weight of the reduced chromium slag) and 48 kg of composite alkali activator (12% of the dry weight of the reduced chromium slag) were added to the reduced chromium slag slurry obtained from S1. The composite alkali activator was prepared by pre-mixing sodium hydroxide, water glass (modulus 2.3), and calcium hydroxide in a mass ratio of 4:5:1.5. The mixture was stirred at 300 r / min for 20 min to obtain a homogeneous alkali-activated slurry.

[0052] The alkali-activated slurry was pumped into a diaphragm filter press and cured under a pressure of 2.0 MPa for 30 minutes. The resulting solidified block had a moisture content of 13.5%. After demolding, the solidified block was placed in a standard curing room (temperature 20±2℃, relative humidity ≥95%) for 28 days. After 28 days of curing, the solidified block was tested and found to have a compressive strength of 34.2 MPa. All heavy metal leaching toxicity indicators met the limits specified in the "Identification Standard for Hazardous Waste - Leaching Toxicity Identification" (GB5085.3).

[0053] S3 Stone-like Concrete Preparation The solidified blocks obtained from S2 were crushed by an impact crusher and classified by a vibrating screen to obtain coarse aggregate of 5-10mm solidified blocks and fine aggregate of 0.15-4.75mm solidified blocks. Separately, river dredging silt was naturally dried, crushed, and sieved through a 4.75mm screen to obtain fine aggregate containing mud. Testing showed that its silt content was 30% (by weight), SiO2 content was 42%, and moisture content was 48%.

[0054] Weigh the raw materials according to the following mass ratio: 35 parts coarse aggregate of solidified blocks, 25 parts fine aggregate of solidified blocks, 15 parts fine aggregate containing mud, 20 parts P·O42.5 ordinary Portland cement, 8 parts S95 grade slag powder, 0.16 parts polycarboxylate superplasticizer (water reduction rate 28%) (0.8% of cement mass), and 10 parts water. Put the above raw materials into a forced mixer and mix for 3 minutes to obtain a uniform mixture.

[0055] The mixture is poured into a stone-like paving brick mold and placed in a vacuum filter press molding machine. It is then pressed for 15 minutes under a vacuum of -0.08 MPa and a pressure of 1.5 MPa to complete the molding process. After demolding, the green body is sent to a standard curing room (temperature 20±2℃, relative humidity ≥95%) for curing for 28 days to obtain the stone-like concrete paving brick.

[0056] In this embodiment, the performance of the prepared stone-like concrete paving bricks or panels was tested, and the results are as follows: 28-day compressive strength: 43.6 MPa; 28-day flexural strength: 4.5 MPa; Freeze-thaw resistance rating: F200 (weight loss rate <5%, strength loss rate <25%). Permeability grade: P8; Hexavalent chromium leaching concentration: 0.032 mg / L (tested according to HJ / T299 "Identification of Toxicity of Leaching from Solid Waste by Sulfuric Acid and Nitric Acid Method").

[0057] All performance indicators meet the requirements of JC / T446-2000 "Concrete Pavement Bricks" and GB5085.3, and can be used as municipal road paving and landscape decorative panels.

[0058] In this embodiment, the specific performance test results are shown in Table 1.

[0059] Example 3 This embodiment is another specific implementation of Embodiment 1.

[0060] In this embodiment, the specific steps of the method for producing imitation stone concrete paving bricks and panels are as follows: S1 Take wet chromium slag with a hexavalent chromium content of 2800 mg / kg, adjust the pH of the slurry to 2.0, add isosorbide:hexavalent chromium at a mass ratio of 5:1, react at 90℃ for 2 hours, and the filtrate contains 0.08 mg / L of hexavalent chromium.

[0061] S2 fly ash content 40%, alkali activator ratio NaOH:water glass:Ca(OH)2=2:5:2, total content 15%, 2.5MPa pressure filtration for 20min, solidified block moisture content 14%, 28d strength 32MPa.

[0062] S3 coarse aggregate 40 parts, fine aggregate 20 parts, mud-containing fine aggregate 10 parts (silt content 25%), cement 25 parts, slag powder 5 parts, water 8 parts, vacuum pressure filtration parameters -0.06MPa / 2.0MPa / 10min, steam curing at 60℃ / 8h, then standard curing for 28 days.

[0063] In this embodiment, the performance of the prepared stone-like concrete paving bricks or panels was tested, and the results were as follows: the compressive strength of the finished product was 42 MPa, the flexural strength was 4.1 MPa, and the hexavalent chromium leaching was 0.04 mg / L.

[0064] In this embodiment, the specific performance test results are shown in Table 1.

[0065] Example 4 This embodiment is another specific implementation of Embodiment 1.

[0066] In this embodiment, the specific steps of the method for producing imitation stone concrete paving bricks and panels are as follows: S1 Take chromium slag with a hexavalent chromium content of 600 mg / kg, adjust the pH of the slurry to 2.5, add isosorbide:hexavalent chromium in a mass ratio of 3:1, react at 80℃ for 4 hours, and the filtrate contains 0.02 mg / L of hexavalent chromium.

[0067] S2 fly ash content 20%, alkali activator ratio NaOH:water glass:Ca(OH)2=1:3:1, total content 8%, 1.5MPa pressure filtration for 40min, solidified block moisture content 15%, 28d strength 30MPa.

[0068] S3 coarse aggregate 30 parts, fine aggregate 30 parts, mud-containing fine aggregate 20 parts (silt content 35%), cement 15 parts, slag powder 10 parts, water 12 parts, vacuum pressure filter -0.09MPa / 1.0MPa / 20min, standard curing 28d.

[0069] In this embodiment, the performance of the prepared stone-like concrete paving bricks or panels was tested, and the results were as follows: the compressive strength of the finished product was 45 MPa, the flexural strength was 4.8 MPa, and the hexavalent chromium leaching was 0.02 mg / L.

[0070] In this embodiment, the specific performance test results are shown in Table 1.

[0071] Comparative Example 1 In this comparative example, except that isosorbide was replaced with an equimolar amount of ferrous sulfate in step S1, all other conditions were the same as in Example 2. The preparation method was the same as in Example 2.

[0072] In this comparative example, the performance of the prepared stone-like concrete paving bricks or panels was tested. The results were as follows: the concentration of hexavalent chromium in the filtrate was 0.35 mg / L (exceeding the standard), the 28-day strength of the cured block was only 22 MPa, the hexavalent chromium leaching of the finished paving bricks was 0.18 mg / L (exceeding the limit of GB5085.3), and obvious yellow spots appeared on the surface.

[0073] In this comparative example, the specific performance test results are shown in Table 1. Table 1 In summary, as shown by the comparative data in Table 1, under the process conditions described in this invention, when isosorbide is used as the reducing agent alone, the removal rate of hexavalent chromium reaches 99.6%, the leaching concentration is as low as 0.032 mg / L, and the resulting concrete has a 28-day compressive strength of 43.6 MPa and a flexural strength of 4.5 MPa, simultaneously meeting the requirements for environmental safety and mechanical performance.

[0074] The above description is merely a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the concept described herein through the above teachings or related technologies or knowledge. Modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.

Claims

1. A method for producing stone-like concrete paving bricks and panels by reducing chromium slag, characterized in that, Includes the following steps: S1 Chromium Slag Deep Reduction and Detoxification: The original chromium slag is crushed and ground to a particle size ≤0.075mm, and then calcined and activated at 400-450℃ for 1-2 hours to obtain activated chromium slag powder. The activated chromium slag powder is mixed with water at a mass ratio of 1:1.5-3 to form a slurry. The pH of the slurry is adjusted to 2.0-2.5, and isosorbide is added as a reducing agent. The mixture is stirred and reacted at 80-90℃ for 2-4 hours. During the reaction, samples are taken every 30-40 minutes to detect the hexavalent chromium content until the hexavalent chromium concentration in the filtrate is ≤0.1mg / L, thus reducing hexavalent chromium to trivalent chromium, resulting in a reduced chromium slag slurry. The removal rate of hexavalent chromium in the filtrate of the reduced chromium slag slurry is ≥99.5%. The mass ratio of isosorbide to hexavalent chromium in the original chromium slag is (3-5):1; S2 Alkali Activation-Filtration Coupled Curing: Fly ash and composite alkali activator are added to the reduced chromium slag slurry obtained in step S1, and the mixture is stirred evenly to obtain an alkali-activated slurry; the alkali-activated slurry is injected into a diaphragm filter press and cured under a pressure of 1.5-2.5 MPa for 20-40 min. After demolding, the resulting cured block is cured for 28 days at a temperature of 20±2℃ and a relative humidity of ≥95% to obtain a cured block with a moisture content of ≤15%; the composite alkali activator is composed of sodium hydroxide, water glass and calcium hydroxide; Preparation of S3 imitation stone concrete: The solidified blocks obtained in step S2 are crushed and sieved to obtain coarse aggregate and fine aggregate of solidified blocks; by mass, take 30-40 parts of coarse aggregate, 20-30 parts of fine aggregate, 10-20 parts of mud-containing fine aggregate, 15-25 parts of cement, 5-10 parts of slag powder, and 8-12 parts of water, mix them evenly, and pour them into a mold. After vacuum pressing and filtration, and curing, imitation stone concrete paving bricks or panels are obtained; the silt content in the mud-containing fine aggregate is 25%-35% by mass.

2. The method for producing imitation stone concrete paving bricks and panels using reduced chromium slag according to claim 1, characterized in that, The original chromium slag mentioned in step S1 is wet or dry chromium slag that has not undergone high-temperature melting treatment, and its hexavalent chromium content is 500-3000 mg / kg; the isosorbide is self-made high-purity isosorbide with a purity ≥99%; the preparation method of isosorbide is as follows: using glucose as raw material, catalytic hydrogenation is carried out in the presence of Raney nickel catalyst at 3.0-3.2 MPa and 110-120℃, and the reaction product is decolorized by activated carbon, concentrated under reduced pressure to a solid content of 70%, and then crystallized and dried; the amount of Raney nickel catalyst added is 5% of the glucose mass.

3. The method for producing imitation stone concrete paving bricks and panels using reduced chromium slag according to claim 1, characterized in that, The fly ash mentioned in step S2 is grade II or above fly ash, and the dosage is 20%-40% of the dry weight of the reduced chromium slag; the mass ratio of sodium hydroxide, water glass and calcium hydroxide in the composite alkali activator is (3-5):(4-6):(1-2), wherein the modulus of water glass is 2.0-2.5; the total dosage of the composite alkali activator is 8%-15% of the dry weight of the reduced chromium slag.

4. The method for producing stone-like concrete paving bricks and panels by reducing chromium slag according to claim 1, characterized in that, The 28-day compressive strength of the cured block obtained in step S2 is ≥30MPa, and the leaching toxicity of heavy metals meets the limit requirements of GB5085.3-2007 "Identification Standard for Hazardous Waste - Leaching Toxicity Identification".

5. The method for producing imitation stone concrete paving bricks and panels using reduced chromium slag according to claim 1, characterized in that, The fine aggregate containing mud in step S3 is obtained by naturally drying, crushing and sieving river dredging silt or engineering waste soil, with a particle size ≤4.75mm, and the SiO2 content in the silt ≤50% and the moisture content ≤60%; the cement is P·O42.5 ordinary Portland cement; the mixed raw materials also contain polycarboxylate superplasticizer, the water reduction rate of the polycarboxylate superplasticizer is ≥25%, and the dosage is 0.5%-1.0% of the cement mass.

6. The method for producing imitation stone concrete paving bricks and panels using reduced chromium slag according to claim 1, characterized in that, The process parameters for vacuum pressure filtration molding in step S3 are: vacuum degree -0.06-0.09MPa, pressure 1.0-2.0MPa, and holding time 10-20min.

7. The method for producing imitation stone concrete paving bricks and panels using reduced chromium slag according to claim 1, characterized in that, The maintenance described in step S3 can be carried out in any of the following ways: Standard maintenance: temperature 20±2℃, relative humidity ≥95%, maintenance period 7-28 days; Steam curing: Temperature 60-80℃, curing for 6-12 hours, then switch to standard curing until 28 days old.

8. The method for producing imitation stone concrete paving bricks and panels using reduced chromium slag according to claim 1, characterized in that, The 28-day compressive strength of the imitation stone concrete paving bricks or panels obtained in step S3 is ≥40MPa, the flexural strength is ≥4.0MPa, and the hexavalent chromium leaching concentration is ≤0.05mg / L; the test method for the hexavalent chromium leaching concentration is performed in accordance with HJ / T299 "Identification of Leaching Toxicity of Solid Waste by Sulfuric Acid and Nitric Acid Method".

9. The stone-like concrete paving bricks and panels prepared by the method for producing stone-like concrete paving bricks and panels by reducing chromium slag according to any one of claims 1-8.

Citation Information

Patent Citations

  • A reconstructed chromium slag powder for radiation-shielding mortar and concrete, and its preparation and application.

    CN108439836B

  • High-strength concrete taking carbon chromium slag as main aggregate, processing device and preparation process of high-strength concrete

    CN114804814A

  • Photovoltaic cast-in-place pile concrete taking composite activated chromium slag as admixture and preparation method of photovoltaic cast-in-place pile concrete

    CN119080452A